2014
DOI: 10.1002/macp.201400452
|View full text |Cite
|
Sign up to set email alerts
|

Toward a New Family of Bifunctional Organoiron Dendrimers: Facile Synthesis, Redox, and Photophysical Fingerprints

Abstract: Multifunctional macromolecules continue to attract attention. Here, three generations of a new family of bifunctional organoiron dendrimers are reported, which are synthesized from a redox-active organoiron complex, η 6 -dichlorobenzene-η 5 -cyclopentadienyl-iron(II). The facile chemistry of the complex is exploited to functionalize the dendritic peripheral with photoactive β-naphthol, yielding redox, photoactive dendrimers under mild conditions. To ascertain the redox and photophysical fi ngerprints of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 71 publications
(106 reference statements)
3
33
0
Order By: Relevance
“…Typical of macromolecules derived from η 6 ‐dichlorobenzene‐η 5 ‐cyclopentadienyliron(II) complex, all the dendrimers were thermally stable up to 200 °C and degraded in three steps (Figure A). The first onset temperature ( T onset ) corresponds to cleavage of the cyclopentadienyliron(II) moieties and the subsequent thermal decomposition of the cyclopentadienyl ring as previously proved . The resulting organic dendrimer‐iron composite was stable up to 380 °C, after which rapid weight loss and volatilization occurred at the second and third T onset , respectively (Figure A).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Typical of macromolecules derived from η 6 ‐dichlorobenzene‐η 5 ‐cyclopentadienyliron(II) complex, all the dendrimers were thermally stable up to 200 °C and degraded in three steps (Figure A). The first onset temperature ( T onset ) corresponds to cleavage of the cyclopentadienyliron(II) moieties and the subsequent thermal decomposition of the cyclopentadienyl ring as previously proved . The resulting organic dendrimer‐iron composite was stable up to 380 °C, after which rapid weight loss and volatilization occurred at the second and third T onset , respectively (Figure A).…”
Section: Resultssupporting
confidence: 58%
“…As an example, the nonequivalent protons of the iron‐complexed chlorobenzene that resonated at 6.76 and 6.38 ppm shifted upfield to 6.21 ppm, resonating as a single broad peak (Figure SI1, Supporting Information) of equivalent protons after S N Ar reaction of DEN1 with 5(4‐hydroxyl)phenylpentanoic acid. Previously, we have shown that the splitting pattern and resonance frequencies of the iron‐complexed chlorobenzene change after S N Ar reaction of the chloro group . Moreover, the appearance and disappearance of peaks attributed to functional groups were diagnostic tools to monitor the successes of the synthesis steps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic route to the dendrimers is straightforward, exploiting the reactivity of η 6 ‐arene‐ η 5 ‐cyclopentadienyliron(II) toward a wide range of nucleophiles . For instance, to construct 0‐DEN‐TPE/DPP , η 6 ‐dichlorobenzene‐ η 5 ‐cyclopentadienyliron(II) was reacted with 4,4‐bis(4‐hydroxyphenyl)valeric acid via K 2 CO 3 ‐mediated nucleophilic aromatic substitution reaction (S N Ar), accessing the bimetallic building block (Scheme S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Metallodendrimers [1][2][3][4][5][6] have attracted much attention as catalysts, [4][5][6][7][8][9][10][11][12] sensors, [13] and nanomaterials, [5] but nanoparticle-cored (NP-cored) dendrimers, that is, NPs decorated with dendrons, have relatively rarely been reported and examined. [14][15][16][17][18][19][20][21][22] Transition metal NPs, [23,24] in particular palladium NPs (PdNPs), [25][26][27][28][29][30][31] under a large variety of forms have been applied as catalysts for organic reactions and attracted considerable interest for years.…”
Section: Introductionmentioning
confidence: 99%